Colchicine-induced apoptosis daily rhythms in male and female suckling mice - González, Norma Viviana (2011)
Cell death in the intestinal crypts is increased in many conditions including exposure to several cytotoxic compounds, among them colchicine. In despite of in vitro studies´ abundance, in vivo investigations assessing the effect of this microtubule inhibitor on apoptosis are scarce and no data dealing specifically with colchicine-induced apoptosis in suckling mice are available. The aims were to determine the colchicine inductive effect on apoptosis in 14 d old mice intestinal crypts; to establish the existence of daily variations in the apoptotic indices and to examine whether there is sexual dimorphism in such variations. Experimental work was performed on C3H/S male and female 14 d old mice exposed to 12:12 light-dark conditions. Commencing at midnight and every 4 h thereafter animals were sacrificed having received an i.p. 1 µg colchicine dose per g body weight 4 h before. Samples of duodenum and colon were processed for hematoxylineosin staining and TUNEL technique. Twenty longitudinally sectioned crypts per organ and individual were monitored for apoptotic cells. The apoptotic index was expressed as the number of apoptotic cells per 1,000 nuclei for each animal. The arithmetic mean ± SE was calculated for each study time and gender. Differences between genders were determined by the Student’s t test. Within group differences were tested by one-way analysis of variance (ANOVA). Results revealed that. 1) the apoptotic daily changes phasing in the small bowel between young males and females showed sexual dimorphism; 2) the absence of daily variations in the young female large bowel cell death indices; 3) a highly prominent induced apoptosis intensity in the small bowel; 4) the sensitivity and number of colchicine induced-apoptosis changes throughout the day are age-dependant. Colchicine is to be taken regularly as a treatment for various human diseases and poisoning results in a multi-organ dysfunction syndrome, particularly affecting tissues with rapid cell turnover among them the intestinal epithelium. The complex pattern of variables implied in the colchicine-induced intestinal apoptosis rhythms (gender, age, time of drug delivery) highlights the need of treatments design with colchicine dosing according with the patient condition.